Depathologising female depression: colonising women’s psychic space in Celeste Ng’s Everything I Never Told You - Zhou, Qiaoqiao; Omar, Noritah (Department of English Language and Literature, International Islamic University Malaysia, 2022)
Women have long been disproportionally pathologised as melancholic or depressive as if they are naturally passive or deficient. Specifically, depressed mothers are usually believed to be responsible for their children’s abnormality. Celeste Ng’s novel Everything I Never Told You (2014) portrays similar predicaments of three generations of mothers and daughters. While many researchers mostly blame mothers for their daughters’ depression and/or suicide, they fail to explain the vicious cycle that perpetuates the blame-the-mother myth and more specifically, the mechanism of social oppression in stigmatising women. Using Kelly Oliver’s conceptualisation of social melancholy and colonisation of psychic space, this study explores the relationship between social complexity and its consequences on the psychic space of women. This study argues that Ng’s female subjects suffer “social melancholy” as a result of the colonisation of their psychic spaces. Without a supportive social space where positive representations of womanhood and motherhood are valued, those female subjects regard themselves as defective and depressed. The reductionist attribution of responsibility to the mothers is criticised, as it risks individualising and decontextualising the pathology of society in denigrating women in general and mothers in particular, and ultimately rendering them depressive and even suicidal.